(untitled) (Research, Society and Development, 2022)
This article aims to report the experience of an extension project that made it possible to encourage the prevention of skin cancer. The study it was carried out in the municipalities of the Amazon region, including: Altamira/PA, Ananindeua/PA; Belem/PA; Cametá/PA; Parauapebas/PA and Porto Velho/RO, in person and online. The causes, symptoms, diagnosis and prophylaxis of Skin Cancer were exposed, with the help of illustrative pamphlets. 868 participants were reached, in places with high insolation, and we sought to know the users’ perception of skin cancer prevention practices and their knowledge about the subject. Regarding the audience reached, differences were observed in the number of people, variations in age and gender of the participants, depending on the location chosen for carrying out the actions. In addition, the moment of interaction with research participants provided the exchange of knowledge and the offer of instructions on how to act in face of daily sun exposure. It is understood that health education extension actions are essential to contribute to the prevention of skin cancer and to the relationship between the academic environment and the population.